Pengaruh Metode Pembelajaran dan Berpikir Kritis Terhadap Hasil Belajar Sejarah Siswa SMA Kesatuan Bogor - Iin Iryance (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2014)
Absrtact The aim of the study is to reveal the empirical data about the effect of instructional methodology and student’s critical thinking capability level on the outcome of history learning on the students of SMA Kesatuan Bogor. The methodology used is the experimental method with a 2x2 factorial design. Research instrumentation will include a test that will be used to measure student’s learning outcome, and a questionnaire that will be used to measure student’s critical thinking capability level on history outcomes. A total of 28 participants will be randomly selected. Data analysis will be performed by using two way variance analysis. The findings of the study will be demonstrate: 1) a higher student’s history learning outcome of those who were taught by PJBL instructional methodology compared to those who were taught by conventional method. 2) There is an interaction effect between instructional methodology and student’s critical thinking level on history learning outcome. 3) History learning outcome of students who has higher critical thinking level and were taught by PJBL method are higher than those with the same level of critical thinking but were taught by conventional method. 4) History learning outcome of students who has lower critical thinking level and were taught by PJBL methodology are not below those with the same critical thinking but were taught by conventional method. Keywords : history learning outcome, instructional methodology, student’s critical thinking